How Leadership and Quality of Work Life (QWL) Drive Employee Performance in Public Hospitals - Mella Mardayanti; Fangela Myas Sari; Reza Rahmadi Hasibuan; Dian Priatiningsih (El-Barka Journal of Islamic Economics and Business, 2025)
This study investigates how leadership and quality of work life contribute to improving employee performance in public hospitals, with a case study at RS QIM Batang, Central Java. The research focuses on employees working in the service department. A causal-associative quantitative design was employed, involving 100 respondents selected from a total population of 237 employees through stratified random sampling. Data were analyzed using the Structural Equation Modeling (SEM) approach with WarpPLS 8.0 software. The results indicate that leadership positively and significantly affects employee performance. Likewise, the quality of work life shows a positive and significant relationship with performance, while organizational commitment has a positive yet the quality of work life (QWL) has a statistically insignificant yet contextually relevant influence on employee performance at RS QIM Batang, reflecting the need for stronger alignment with Islamic work values.